Spatiotemporal agent-based model explorations of white-tailed deer management in New England - Kohler, Allison M., author; Boone, Randall B., advisor; Childers, Michael, committee member; Van Deelen, Timothy, committee member; Lynn, Stacy, committee member (Colorado State University. Libraries, 2023)
This dissertation research addresses the intricate challenge of managing white-tailed deer (Odocoileus virginianus, henceforth "WTD") populations in the New England region while considering evolving ecological dynamics, changing interests of various stakeholders, and the role of management coordination among municipalities across scales. With a mixed-methods approach, I integrate qualitative and quantitative techniques such as agent-based modeling and case study analysis, helping to contribute multifaceted insights into the realm of WTD management in the region. In Chapter 2, I focus on investigating the role of hunter recruitment and land access in shaping local WTD populations across 11 focal towns in New England. The purpose of this chapter is to explore how these factors influence WTD populations, specifically by identifying the thresholds at which they become significant drivers in controlling these populations. To achieve this, I employ a mixed-methods approach that combines ecological modeling and the analysis of empirical data. The study's results emphasize the specific thresholds of hunting land access required to trigger a decline in WTD populations for different hunter density scenarios. I estimate that in most towns, the existing combination of hunter density and land access is effective in managing local WTD populations. However, under conditions of declining hunter recruitment, towns may require higher amounts of hunting access to achieve similar levels of population control. These findings underscore the significance of addressing issues related to declining hunter numbers and enhancing opportunities for hunting to sustain effective deer population management the region. This chapter's implications stress the importance of adaptive strategies and community engagement in the realm of WTD management in New England. In Chapter 3, I assess the role of sharpshooting as a potential urban WTD management strategy across various contexts in New England. The chapter's primary purpose is to examine the feasibility of sharpshooting when factors like declining hunter numbers and limited hunting land access impact the efficacy of current deer management approaches. I conduct this investigation using a mixed-methods approach, combining ecological modeling with social science surveys and assessments. The results from this chapter offer insights into the role of sharpshooting as a strategy if the effectiveness of hunting diminishes. The findings suggest that most of the towns studied can effectively manage WTD populations without the need for sharpshooting. However, as hunter recruitment declines and hunting access becomes more limited, sharpshooting may become a reasonable solution when it aligns with community preferences. This chapter concludes that sharpshooting can serve as a management tool in certain scenarios, emphasizing the significance of prioritizing stakeholder education, engagement, and acceptance. The implications drawn from this research underscore the need for community involvement in shaping management decisions, particularly in relation to adopting sharpshooting for local WTD population control. In Chapter 4, I focus on the broader theme of WTD management coordination in New England, examining its implications in controlling WTD populations across spatial scales. The main purpose of this chapter is to assess the impacts of stakeholder cooperation and coordination among municipalities on the effectiveness of WTD population management. My methodology involves the development and application of theoretical agent-based models to simulate different coordination scenarios. The chapter's results consistently demonstrate the significant role of coordination in shaping management outcomes, both within individual towns and across multiple municipalities. Based on model outcomes, effective cooperation between neighboring towns consistently leads to lower WTD densities both in towns with and without active management, exemplifying the role of collaborative efforts at larger scales. Additionally, the findings highlight the need for flexible strategies that consider the unique circumstances of each municipality. When aligned with community interests, the results demonstrate the potential for significant reductions in WTD densities with coordinated lethal management efforts, offering a path for more successful WTD population management in New England and similar regions. The implications of this chapter emphasize the role of regional cooperation and the importance of tailoring management strategies to specific contexts and community dynamics. This research not only contributes insights into the complexity of WTD management in New England, but it also serves as a broader blueprint for wildlife management worldwide. I encourage other researchers to build agent-based models to inform management of other situations and species across geographical locations and contexts. In this research, I reveal that the challenge of managing WTD populations largely arises from the spatially heterogeneous distribution of WTD and resulting conflicts, in addition to the complexity of achieving stakeholder consensus across spatial scales. This demonstrates the tradeoff between accommodating diverse stakeholders and achieving regional WTD population control. With adaptive, science-based, and community-based approaches, I explore the roles of adaptability, collaboration, and innovation in contributing to sustainable WTD management efforts. In the end, I hope this research contributes to informing management practices, promoting a balanced and harmonious coexistence between humans and resident wildlife in a changing world.
Keywords: ecology; Odocoileus virginianus; wildlife management; management coordination; coupled natural-human systems; white-tailed deer